Metal-fullerene on materials for electronics - M, E.M.Shpilevsky; P. Tuvshintur,; S.A.Filatov,; G. Shilagardi,; D.Tumurbaatar, (Scientific transaction of the National University of Mongolia. Physics, 2022)
The results of studying the physical properties of film materials containing metals and fullerenes are presented. It is shown that the use of these materials in electronics, optoelectronics, biomedicine significantly increases the capabilities of tools and mechanisms.